The Constitutionality of Coercive Measures in The Preliminary Investigation of Tax Offense - Nafis Dwi Kartiko (Journal of Constitutional and Governance Studies, 2025)
This study aims to analyse the implications of coercive measures in the investigation of preliminary evidence regulated by Article 43A paragraph (1) and paragraph (4) of Article 2 number 13 of the HPP Law on the principle of the rule of law and legal certainty in the enforcement of tax criminal law. Using a normative-dogmatic legal approach, this study examines relevant legal norms and doctrines, focusing on positive law and the Constitutional Court’s decision Number 83/PUU-XXI/2023. This methodology allows for an in-depth analysis of the applicable legal framework and its impact on taxpayer rights. The results of the study show that there is no legal mechanism for taxpayers to challenge coercive efforts to create legal uncertainty, contrary to the principles of justice, equality before the law, and the protection of human rights. This undermines trust in the legal system and requires clarity on legal remedies available to taxpayers. This research highlights the importance of integrating human rights into tax legislation, in accordance with international standards and the 1945 Constitution, to ensure that tax regulations are aligned with the principles of justice, equality before the law, and legal certainty. The conclusion of this study emphasizes the need for a clear, fair, and consistent legal framework to strengthen public trust in the tax system and the government, as well as to support the active participation of taxpayers in tax policy making. Keywords: Taxation, Investigation of Preliminary Evidence, Tax Offences Abstrak Penelitian ini bertujuan untuk menganalisis implikasi dari upaya paksa dalam pemeriksaan bukti permulaan yang diatur dalam Pasal 43A ayat (1) dan ayat (4) Pasal 2 angka 13 UU HPP terhadap prinsip negara hukum dan kepastian hukum dalam penegakan hukum pidana perpajakan. Penelitian ini menggunakan pendekatan yuridis normatif-dogmatik, yang mana mengkaji norma-norma hukum dan doktrin yang relevan, berfokus pada hukum positif dan putusan Mahkamah Konstitusi Nomor 83/PUU-XXI/2023. Metodologi yang digunakan memungkinkan analisis mendalam terhadap kerangka hukum yang berlaku serta implikasinya terhadap hak-hak para wajib pajak. Hasil penelitian menunjukkan ketiadaan mekanisme hukum bagi wajib pajak untuk menantang upaya paksa menciptakan ketidakpastian hukum, bertentangan dengan prinsip-prinsip keadilan, kesetaraan di hadapan hukum, dan perlindungan hak asasi manusia. Hal ini menggerogoti kepercayaan terhadap sistem hukum dan membutuhkan kejelasan tindakan hukum yang dapat diambil oleh wajib pajak. Penelitian ini menyoroti pentingnya integrasi hak asasi manusia dalam peraturan perpajakan, sesuai dengan standar internasional dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, memastikan bahwa peraturan perpajakan selaras dengan prinsip keadilan, kesetaraan di mata hukum, dan kepastian hukum. Kesimpulan penelitian ini menekankan perlunya kerangka hukum yang jelas, adil, dan konsisten untuk memperkuat kepercayaan publik terhadap sistem perpajakan dan pemerintahan, serta mendukung partisipasi aktif wajib pajak dalam pembuatan kebijakan perpajakan. Kata kunci: Perpajakan, Pemeriksaan Bukti Permulaan, Tindak Pidana Perpajakan